A profile of patients attending the medicine service in a public hospital - Contreras Camarena, Carlos Walter (2009)
Introduction: The diversity of health needs in a national general hospital puts a heavy pressure on both medical assistance and administrative management. Knowing the pathologic and demographic profile of hospitalized patients in the Department of Medicine may allow us to plan future investments in infrastructure, logistics, equipment, and healthcare personnel, and it may also facilitate an appropriate resource allocation, improving both availability and quality of services. Objectives: To determine the profile of patients hospitalized in the Department of Medicine. Material and method: This is a descriptive, observational, and cross-sectional study. A systematic sample including 372 clinical records was chosen, from 9,959 total hospitalizations during 2006 and 2007. The following variables were collected: age, sex, diagnosis, time and day of hospitalization, outcome, and hospital stay. The following parameters were determined: absolute and relative rates, standard deviation, mean, median, and variance. Results: The main reasons for hospitalization were: gastrointestinal, 11.56%; pulmonary, 11.02%; cardiovascular, 9.67%; endocrine, 8.60%; hematological, 5.37%; kidney, 4.84%; neurological, 4.03%; rheumatic, 2.93%; infectious, 2.68%; psychiatric, 1.88%; neoplastic, 1.07%; and dermatological diseases, 0.83%. Conclusions: Hospitalized patients in the Department of Medicine are often independent workers, poor, halfway in school and predominantly affected by predominantly a gastrointestinal, cardiac and respiratory, and endocrine diseases. The greatest demand of hospitalizations takes place on Tuesday mornings, and the average hospital stay is 14.23 days. stay mean.